Cyber-security culture towards digital marketing communications among small and medium-sized (SME)entrepreneurs / by Aiman Huzrin Adleena Huzaizi, Siti Nor Amalina Ahmad Tajuddin, Khairul Azam Bahari, Kamaruzzaman Abdul Manan & Nur Nadia Abd Mubin - Siti Nor Amalina Ahmad Tajuddin (Tanjong Malim, 2021)
Cyber-security culture towards digital marketing communications among small and medium-sized (SME)entrepreneurs / by Aiman Huzrin Adleena Huzaizi, Siti Nor Amalina Ahmad Tajuddin, Khairul Azam Bahari, Kamaruzzaman Abdul Manan & Nur Nadia Abd Mubin by Siti Nor Amalina Ahmad Tajuddin